Tipos y causas del maltrato infantil asociado al rol del agresor en el contexto familiar: Revisión Sistemática - Ramón Tocto, Doris Estefanía (2024)
Child abuse is any deliberate or negligent action that harms the rights, well-being and besides the social, physical mental or development of a child. This research had as a main objective to determine the scientific evidence of the types and causes of child abuse associated with the role of the aggressor in the family context. To identify the types and causes of child abuse. To know the role of the aggressor and design a psychoeducational guide that responds to the research findings. In order to develop this research, a non-experimental quantitative approach along a crosssectional design with a descriptive scope was used. Likewise, the bibliographic synthesis method was implemented. The study population included the scientific literature which was available in several databases such as: Proquest, Pubmed, Dialnet, Scielo and Redalyc, and selection criteria were applied by forming a sample that included 15 documents. The results revealed that, within the family environment, child abuse manifests itself mainly as psychological abuse and neglect because of abandonment. All these, followed by physical and sexual abuse. Furthermore, some key factors such as previous experiences of parental abuse, family violence, substance use, poor academic performance of children, and economic difficulties, become fundamental causes of child abuse. It was also evident that both the parents together and the mother separately play the role of aggressors. In this way, it was concluded that child abuse in the family environment it is manifested mainly as psychological abuse and negligence, alongside key causes which are associated with family and socioeconomic factors